2003
DOI: 10.1253/circj.67.793
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Capillary Hemangiomatosis With Severe Pulmonary Hypertension

Abstract: 25-year-old man presented in 1998 with the complaint of progressive dyspnea on exertion and was admitted to hospital in August 1999. Cardiac catheterization revealed moderate pulmonary hypertension (PH; pulmonary artery pressure 61/33 mmHg). Congenital heart disease and left-sided heart failure were excluded by echocardiography. Collagen disease and liver disease were ruled out by negative results for the autoantibody test and liver function test. Furthermore, a perfusion lung scan did not show any perfusion d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 10 publications
0
22
0
1
Order By: Relevance
“…Progressive dyspnea and fatigue characterize the clinical manifestations of both PVOD and PCH, which are thus typically misdiagnosed as pulmonary arterial hypertension (PAH) (1,10,(13)(14)(15). Patients may also have chronic cough (dry or pro-ductive), chest pain, syncope, or digital clubbing (1,6,15).…”
Section: Deceptive Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Progressive dyspnea and fatigue characterize the clinical manifestations of both PVOD and PCH, which are thus typically misdiagnosed as pulmonary arterial hypertension (PAH) (1,10,(13)(14)(15). Patients may also have chronic cough (dry or pro-ductive), chest pain, syncope, or digital clubbing (1,6,15).…”
Section: Deceptive Clinical Presentationmentioning
confidence: 99%
“…In PCH, the age range of affected patients is broad (2-71 years), with a mean age of 30 years, which is comparable to the age range of patients with PVOD. In contrast to PVOD, however, PCH occurs with equal frequency in both sexes in patients of any age (13)(14)(15). Median survival is 3 years from initial presentation, and, as in PVOD, death may occur only a few months after the onset of symptoms (13,15).…”
Section: Introductionmentioning
confidence: 95%
“…As in patient 1 and also in patient 2, PCH is often associated with PH [9]. Leading clinical symptoms like pulmonary distress and pulmonary hypertension in PCH have to be differentiated from other diseases like hematologic or immunologic diseases [10].…”
Section: Discussionmentioning
confidence: 99%
“…Although this nonspecific symptom is a clinical manifestation of PCH, it is also found with inflammatory alveolitis caused by the CREST syndrome, which was also included in our differential diagnosis. In the setting of primary pulmonary hypertension, the presence of hemoptysis, pleural effusion, elevated number of iron-laden bronchoalveolar macrophages, and an interstitial radiological pattern suggest PCH [2,4,5,6], though there has been at least one report in which pulmonary hypertension was absent in the presence of PCH [6], adding to the difficulty in diagnosing this rare disease. Retrospective analysis of a report by Humbert et al [4] demonstrated that the clinical presentation of PCH is indistinguishable from that of classic hypertensive pulmonary arteriopathy.…”
Section: Discussionmentioning
confidence: 99%